2019
DOI: 10.3390/coatings9040276
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Wear Resistance of 316 L Stainless Steel with a Nanostructured Surface Layer Prepared by Ultrasonic Surface Rolling

Abstract: The low hardness and poor wear resistance of AISI 316 L austenitic stainless-steel sabotage its outer appearance and shorten its service life when it is subjected to sliding. In this paper, the single-pass ultrasonic surface rolling (USR) process was used to modify the surface of 316 L austenitic stainless steel. A nanostructured surface layer with a depth span of 15 μm was fabricated. Dry wear tests of USR samples were performed on a ring-on-block tester at room temperature, and the results were compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Ultrasonic surface rolling (USR), an ultrasonic-based surface nanocrystallization technique, was applied to 316L stainless steel in a study [51]. This process produced a nanostructured surface layer with a thickness of 15 µm, exhibiting higher hardness than the as-received counterpart.…”
Section: Ultrasonic Surface Rolling (Usr) Processmentioning
confidence: 99%
See 2 more Smart Citations
“…Ultrasonic surface rolling (USR), an ultrasonic-based surface nanocrystallization technique, was applied to 316L stainless steel in a study [51]. This process produced a nanostructured surface layer with a thickness of 15 µm, exhibiting higher hardness than the as-received counterpart.…”
Section: Ultrasonic Surface Rolling (Usr) Processmentioning
confidence: 99%
“…However, in the surface-treated alloy, abrasive wear became dominant. Notably, at low sliding speeds, the presence of an oxide film on both the sample and the slider surface heightened the influence of oxidation wear, while at high wear test speeds, direct metal-to-metal contact became the controlling factor in the wear mechanism [51].…”
Section: Ultrasonic Surface Rolling (Usr) Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface mechanical attrition treatment (SMAT) is an SPD technique in which SNC is achieved at the surface of the bulk material. Recently, several researchers have reported improvement in wear resistance and surface hardness by achieving SNC through SMAT [ 23 , 24 , 25 , 26 ]. It has been identified that a high grain boundary density promotes a stable passive film.…”
Section: Introductionmentioning
confidence: 99%
“…A surface modified by an electrical discharge machining method had better anti-fouling performance than a polished surface, which was attributed to an increase in the corrosion resistance and hydrophobicity properties [4]. The USRP is a unique method of mechanical surface treatment that combines ultrasonic impact and static extrusion force [16,17]. It can provide superior surface mechanical properties and surface integrity by decreasing the surface roughness, refining grains, inducing residual compressive stress, and increasing hardness.…”
Section: Introductionmentioning
confidence: 99%